2010
DOI: 10.1021/jp1016054
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Study of the Effect of Silver on the Chelation of Formic Acid to a Titanium Precursor and the Resulting Effect on the Anatase to Rutile Transformation of TiO2

Abstract: Anatase to rutile transition in an unmodified synthetic titania usually occurs at a temperature range of 600-700°C. Various methods such as addition of metallic and nonmetallic dopants and modifying the precursor have previously been reported to influence the anatase to rutile transition temperature. In the current study, the effect of addition of increasing amounts of silver to the extent of chelation of a formate group to a titanium precursor and the resulting effects on the transformation of anatase to ruti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(46 citation statements)
references
References 81 publications
1
45
0
Order By: Relevance
“…An endothermic peak was observed at ∼100 • C for both doped and undoped TiO 2 , which represents unbound water being removed from the TiO 2 surface [16]. However, for undoped TiO 2 the endothermic peak was of greater intensity indicating a greater capacity for the material to absorb water due to increased porosity.…”
Section: Differential Scanning Calorimetrymentioning
confidence: 98%
See 1 more Smart Citation
“…An endothermic peak was observed at ∼100 • C for both doped and undoped TiO 2 , which represents unbound water being removed from the TiO 2 surface [16]. However, for undoped TiO 2 the endothermic peak was of greater intensity indicating a greater capacity for the material to absorb water due to increased porosity.…”
Section: Differential Scanning Calorimetrymentioning
confidence: 98%
“…Anatase and rutile are the most widely investigated polymorphs, with anatase being reported as the most photocatalytically active of the three [3,14,15]. Typically, anatase transforms to rutile under heat treatment (600-700 • C) [16,17]. Parameters that affect the anatase-to-rutile transformation include; particle shape/size [18], source effects [19], atmosphere [20], reaction conditions [21] and purity [22].…”
Section: Introductionmentioning
confidence: 99%
“…TiO 2 exists in nature in three polymorphic forms (anatase, rutile, and brookite), which differ only in the arrangement of their TiO 6 octahedra; anatase (tetragonal) consists of octahedral shearing vertices; rutile (tetragonal) is connected by edges; and in brookite (orthorhombic), both edges and vertices are connected. Thermodynamically, rutile is the most stable phase while both anatase and brookite are metastable, transferring to rutile under heat treatment, typically at temperature ranging between 600 and 700°C [2]. Among the TiO 2 crystalline forms, anatase and rutile are the most widely investigated polymorphs, with anatase generally found to be more photocatalytically active than brookite and rutile, but some reports illustrate the synergistic effect found in the composite mixture of anatase-brookite and anatase-rutile to be responsible for the enhanced photocatalytic activity [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…However, Ihara et al [7] suggested that addition of nitrogen only increases the stabilization of oxygen vacancies and as a consequence helps to improve the visible light activity of N-TiO 2 . While, work by Irie et al [8] showed that nitrogen atoms can be substituted for the lattice oxygen sites to form an isolated impurity energy level (N2p) above the valence band (O2p) of TiO 2 , and under visible light, electrons are excited to the nitrogen impurity energy level. Many other research efforts have also been made with F, S, I, B, Br, C, Cl, and P to develop anionic-doped TiO 2 with improved visible light activity [2,9], and among these nonmetal dopants, sulphur doping in TiO 2 has received much attention due to its anionic (sulfide, S 2− ) and cationic (hexavalent (S 6+ ) and tetravalent (S 4+ )) characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…However, introduction of artificial UV light sources is not practical in remote areas where there is a lack 70 of power supplies. Utilisation of the main part of the solar spectrum by the development of photocatalysts (Figure 2) that can yield high photocatalytic activity under visible light 7,[11][12][13][14][15][16][17][18][19][20][21] would be highly beneficial in remote regions. Hydroxyl radicals have the most positive electrochemical 10 reduction potential (+2.8 V vs. normal hydrogen electrode (NHE)) among other substances generally employed for water disinfection, e.g.…”
Section: Introductionmentioning
confidence: 99%